Le psoriasis chez le nouveau-né et le nourrisson - BELLAHAMMOU KHADIJA (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2012)
Psoriasis is a chronic skin disease characterized by erythematous and scaly lesions affecting about 3 % of the world population and which represents 5 % of child's dermatosis. The family shape is not negligible. It is an inflammatory disease characterized by an abnormal keratinocyte proliferation; it is a complex multifactorial disease involving genetic, immunological and environmental factors; its exact etiology remains badly known. All the clinical forms of the psoriasis can be observed in infant and new born babies. Patch's and drop's psoriasis, psoriasis of the face, psoriasis of the scalp and the napkin psoriasis represent the most frequently aspects observed. The diagnosis of psoriasis is very often clinical and doesn't require any complementary exploration. Psoriasis is usually a benign disease. The grave forms are rare at the new born babies and infants. Its evolution is made by successive pushes with periods of remission more or less long. The treatment is not codified, however the progress realized in understanding the immunopathogenesis led to the development of a range of new treatment options. It is necessary to consider the best evolutionary prognosis for the child. Across our retrospective study interesting infant and new-born babies followed in consultation of child's dermatology in the service of pediatry IV in children's hospital of Rabat over period from 2008 until 2011: 19 cases on the whole kept on clinical criteria. We specified the different clinical aspects, the causes, the treatments and the perspectives of future.
Keywords: INFANT; nouveau-né; PSORIASIS; nourrisson